2002
DOI: 10.1046/j.1365-2230.2002.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of assessments of severity and quality of life in cutaneous disease

Abstract: Clinicians are, by profession, capable assessors of severity of disease. Whether from severity they can deduce a patient's Quality of Life (QoL) is debatable. This study compared scores for physician-assessed severity with the corresponding scores for patient QoL, as assessed using Dermatology Life Quality Index (DLQI) questionnaires in 57 dermatological out-patients. Although there was some degree of correlation between the two measures (r = 0.56), interpretation of QoL from disease severity is clinically unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 4 publications
3
48
2
4
Order By: Relevance
“…Although our study has shown a correlation between selfassessed disease severity (assessed by the GQ), the clinical severity of skin disease does not always correlate with the impact on the patient's quality of life assessed by, for example, the DLQI [29,30] . Although, at a population and individual level, it is sometimes possible to demonstrate a correlation, it is not possible to predict QoL impairment from objective measures, because a variety of individual patient psychological and personal factors also influence the overall QoL impairment.…”
Section: Discussioncontrasting
confidence: 67%
“…Although our study has shown a correlation between selfassessed disease severity (assessed by the GQ), the clinical severity of skin disease does not always correlate with the impact on the patient's quality of life assessed by, for example, the DLQI [29,30] . Although, at a population and individual level, it is sometimes possible to demonstrate a correlation, it is not possible to predict QoL impairment from objective measures, because a variety of individual patient psychological and personal factors also influence the overall QoL impairment.…”
Section: Discussioncontrasting
confidence: 67%
“…Um aspecto relevante das lesões cutâneas da DM do adulto é o impacto na qualidade de vida dos pacientes, resultando em desconforto físico e estresse emocional (15,16) . Tal fato indiscutivelmente é prioritário na população de escolares e adolescentes, uma vez que a imagem corporal é um fator de grande importância na auto-estima desses grupos.…”
Section: Discussionunclassified
“…It has created a social stigma causing loss of the self esteem, social isolation, significant depression, 4 difficulties in sexual relationships and perceived suitability for marriage. 5,6 Previous reports indicated that the patients' illness understanding influences adherence, behaviours and actions in various chronic dermatological conditions. [7][8][9][10][11] To our knowledge, there have been very few studies worldwide regarding vitiligo patients beliefs about their condition.…”
Section: Introductionmentioning
confidence: 99%